2011
DOI: 10.4061/2011/803841
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Disorders in Multiple Sclerosis

Abstract: Multiple sclerosis is an inflammatory disease leading to disseminated lesions of the central nervous system resulting in both somatomotor and autonomic disturbances. These involve the central centers of the autonomic nervous system, as well as the automatic control and pathway systems. All autonomic functions may be disordered individually or in combined form. There is no other disease with a clinical picture so multifaceted. Besides cardiovascular dysfunctions disorders of bladder and rectum have become appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Head-up tilt sleeping position can improve sympathetic activity in patients with sympathetic disturbances [ 92 ]. Patients with orthostatic intolerance may benefit from therapy with volume expanders, vasoconstrictor agents and acetylcholinesterase inhibitors [ 93 , 94 , 95 ]. Sympathomimetic drugs like β-adrenergic agonists, α1-adrenergic agonists and α2-adrenergic antagonists may play an important role in the treatment of patients with lower sympathetic activity [ 88 , 96 , 97 ].…”
Section: Cardiovascular Dysregulationmentioning
confidence: 99%
“…Head-up tilt sleeping position can improve sympathetic activity in patients with sympathetic disturbances [ 92 ]. Patients with orthostatic intolerance may benefit from therapy with volume expanders, vasoconstrictor agents and acetylcholinesterase inhibitors [ 93 , 94 , 95 ]. Sympathomimetic drugs like β-adrenergic agonists, α1-adrenergic agonists and α2-adrenergic antagonists may play an important role in the treatment of patients with lower sympathetic activity [ 88 , 96 , 97 ].…”
Section: Cardiovascular Dysregulationmentioning
confidence: 99%
“…[1][2][3][4][5]8 Neurological disability assessed by Expanded Disability Status Scale Revista Científica da Ordem dos Médicos www.actamedicaportuguesa.com Vieira B, et al Prevalence of autonomic dysfunction in patients with multiple sclerosis, Acta Med Port 2015 Jan-Feb;28(1): [51][52][53][54][55] (EDSS) focuses mainly on the somatic nervous system and undervalues the role of autonomic failure, only taking into account bladder and bowel dysfunction. 1,3,4 Hence, autonomic symptoms can be easily overlooked by exclusive EDSS follow-up. 7 Several studies have suggested the use of questionnaires to evaluate ANSD in order to improve disease management.…”
Section: Introductionmentioning
confidence: 99%
“…1 The autonomic nervous system dysfunction (ANSD) is commonly seen in patients with MS and is characterized by bladder and gastrointestinal disturbances, sexual dysfunction, abnormalities in cardiovascular function and sudomotor disorders. [1][2][3][4][5][6][7] These symptoms may have a significant impact in patients' quality of life and should be explored as part of the routine evaluation. [1][2][3][4][5]8 Neurological disability assessed by Expanded Disability Status Scale Revista Científica da Ordem dos Médicos www.actamedicaportuguesa.com Vieira B, et al Prevalence of autonomic dysfunction in patients with multiple sclerosis, Acta Med Port 2015 Jan-Feb;28(1): [51][52][53][54][55] (EDSS) focuses mainly on the somatic nervous system and undervalues the role of autonomic failure, only taking into account bladder and bowel dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…MS is a demyelinating disease of the central nervous system, characterized by the development of lesions in the brain and spinal cord, which cause widespread neurological symptoms and autonomic dysfunctions such as impaired sphincter control, and impaired sexual response [2,3]. For example, weakness or loss of control of the limbs, sensory symptoms, visual defects, and poor coordination are the most conspicuous symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this study is concerned with the SD in MS patients that is often unaddressed. The specific aims of the study are to (1) analyze the effects of MS on patients' sexual life, (2) investigate the potential relationship between clinical (anxiety, depression) and demographic variables (age, sex) and sexual life in MS patients, (3) identify the coping strategies of MS patients, and (4) determine the relationship between MS patients' coping strategies and their sexual life.…”
Section: Introductionmentioning
confidence: 99%